Physical examination skills training: faculty staff vs. patient instructor feedback - a controlled trial - Krautter, Markus; Schultz, Jobst-Hendrik; Maatouk, Imad; Köhl-Hackert, Nadja; Herzog, Wolfgang; Nikendei, Christoph (PLOS ONE, 2017)
Background Standardized patients are widely used in training of medical students, both in teaching and assessment. They also frequently lead complete training sessions delivering physical examination skills without the aid of faculty teaching staff-acting as “patient instructors” (PIs). An important part of this training is their ability to provide detailed structured feedback to students which has a strong impact on their learning success. Yet, to date no study has assessed the quality of physical examination related feedback by PIs. Therefore, we conducted a randomized controlled study comparing feedback of PIs and faculty staff following a physical examination assessed by students and video assessors. Methods 14 PIs and 14 different faculty staff physicians both delivered feedback to 40 medical students that had performed a physical examination on the respective PI while the physicians observed the performance. The physical examination was rated by two independent video assessors to provide an objective performance standard (gold standard). Feedback of PI and physicians was content analyzed by two different independent video assessors based on a provided checklist and compared to the performance standard. Feedback of PIs and physicians was also rated by medical students and video assessors using a questionnaire consisting of 12 items. Results There was no statistical significant difference concerning overall matching of physician or PI feedback with gold standard ratings by video assessment (p = .219). There was also no statistical difference when focusing only on items that were classified as major key steps (p = .802), mistakes or parts that were left out during physical examination (p = .219) or mistakes in communication items (p = .517). The feedback of physicians was significantly better rated than PI feedback both by students (p = .043) as well as by video assessors (p = .034). Conclusions In summary, our study demonstrates that trained PIs are able to provide feedback of equal quantitative value to that of faculty staff physicians with regard to a physical examination performed on them. However, both the students and the video raters judged the quality of the feedback given by the physicians to be significantly better than that of the PIs.